2002
DOI: 10.1309/6v09-38k3-jq40-ur50
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Survivin in Benign Cervical Mucosa, Cervical Dysplasia, and Invasive Squamous Cell Carcinoma

Abstract: Survivin is an inhibitor of apoptosis protein (IAP) that is expressed in fetal development and in cancer Survivin expression in premalignant lesions remains undefined. We obtained 73 samples of cervical squamous tissue, including 31 normal, 17 low- and 15 high-grade squamous intraepithelial lesions (LSILs, HSILs), and 10 squamous cell carcinomas (SCCs)from cone biopsy and hysterectomy specimens, and stained for survivin using an immunoperoxidase method. Nuclear staining was detected in normal mucosa, LSILs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 12 publications
3
41
0
1
Order By: Relevance
“…The immunostaining was prevalently cytoplasmic in poorly differentiated cases with sporadic prominent nuclear staining in well-differentiated areas, as already reported in cervical mucosa (Frost et al, 2002). However, in this study, differences in the intracellular pattern of staining that resulted were not statistically significant; for this reason, we recorded the specimens as positive without considering the intracellular localisation of the signal (cytoplasmic or nuclear).…”
Section: Survivin Expression In Normal Oral Mucosasupporting
confidence: 45%
“…The immunostaining was prevalently cytoplasmic in poorly differentiated cases with sporadic prominent nuclear staining in well-differentiated areas, as already reported in cervical mucosa (Frost et al, 2002). However, in this study, differences in the intracellular pattern of staining that resulted were not statistically significant; for this reason, we recorded the specimens as positive without considering the intracellular localisation of the signal (cytoplasmic or nuclear).…”
Section: Survivin Expression In Normal Oral Mucosasupporting
confidence: 45%
“…Moreover, in situ hybridisation of serial sections showed the colocalisation of HPV and survivin (Frost et al, 2002). This report indicated that the histologic correlation between nuclear staining of survivin and HPV infection suggests involvement of survivin in HPV-mediated disruption of normal cellular maturation (Frost et al, 2002). However, alternative roles of survivin upregulation in HPV-infected cells may exist (see below).…”
Section: Role Of Survivin In Virus Infection-induced Carcinogenesismentioning
confidence: 71%
“…15,31 However, nuclear accumulation of survivin has been recently described in other human tumors. 32,33 The reason for these differences in cell distribution between tumors is not clear. It has been proposed that the subcellular distribution of survivin is regulated by an active import into the nucleus and a CRM1-mediated export to the cytoplasm, suggesting that survivin may be considered a nuclear shuttling protein.…”
Section: Discussionmentioning
confidence: 99%